Taurine alleviates repression of betaine‐homocysteine S‐methyltransferase and significantly improves the efficacy of long‐term betaine treatment in a mouse model of cystathionine β‐synthase–deficient homocystinuria. Issue 5 (15th February 2019) - Maclean, Kenneth N.; Jiang, Hua; Phinney, Whitney N.; Keating, Amy K.; Hurt, K. Joseph; Stabler, Sally P.
ABSTRACT: Classical cystathionine β‐synthase‐deficient homocystinuria (HCU) is a life‐threatening inborn error of sulfur metabolism. Treatment for pyridoxine‐nonresponsive HCU involves lowering homocysteine (Hcy) with a methionine (Met)‐restricted diet and betaine supplementation. Betaine treatment efficacy diminishes significantly over time due to impairment of betaine‐Hcy S‐methyltransferase (BHMT) function. Little is known regarding the regulation of BHMT in HCU. Using a betaine‐responsive preclinical mouse model of HCU, we observed that this condition induces a 75% repression of BHMT mRNA, protein and enzyme activity, and significant depletion of hepatic betaine levels. BHMT repression was proportional to plasma Hcy levels but was not observed in mouse models of homocystinuria due to either methylenetetrahydrofolate reductase or Met synthase deficiency. Both Met supplementation and chemically induced glutathione depletion exacerbated hepatic BHMT repression in HCU mice but not wild‐type (WT) controls. Conversely, cysteine treatment normalized hepatic BHMT expression in HCU mice but had no effect in WT control animals. Taurine treatment induced BHMT expression in HCU mice by 5‐fold and restored maximal lowering of Hcy levels during long‐term betaine treatment with a concomitant normalization of inflammatory cytokine expression and a significantly improved coagulative phenotype. Collectively, our findings indicate that adjuvantial taurine treatment has the potential to significantly improve clinical outcomes in HCU.—Maclean, K. N., Jiang, H, Phinney, W. N., Keating, A. K., Hurt, K. J., Stabler, S. P. Taurine alleviates repression of betaine‐homocysteine S‐methyltransferase and significantly improves the efficacy of long‐term betaine treatment in a mouse model of cystathionine β‐synthase‐deficient homocystinuria. FASEB J. 33, 6339–6353 (2019). www.fasebj.org